Westward ho! : eleven explorers of the West - Jones, Charlotte Foltz (Holiday House, 2005)
A collective biography of eleven men who explored the American West in the 18th and 19th centuries, including ship's officers, fur traders, and Army officers. These men were searching for a Northwest Passage, exploring the Louisiana Purchase, trapping in the wilderness, mapping the path for Manifest Destiny, and surveying the West.